Вплив аномальних властивостей води на гідроакустичні технології - Гладких, Ігор Іванович; Капочкін, Борис Борисович; Кучеренко, Наталія Василівна; Капочкіна, Маргарита Борисівна (НТУ "ХПІ", 2017)
Виконані дослідження впливу аномальних властивостей морської води на особливості поширення звуку в ній і, навпаки, акустичних хвиль різного частотного діапазону - на фізичні властивості води, що формують феномен наддалекого поширення звуку.

Was investigate the effect anomalous properties of seawater on the characteristics of sound in it. And conversely, acoustic waves of different frequency range -on the physical properties of water that forming, Very long phenomenon of sound in the ocean. Sonar technology used for navigation and for other tasks that require an understanding of the physical principles underlying the phenomena forming the main underwater sound channel and very long propagation in the marine environment. This was considered possible cause some anomalous properties of water, conducted a critical analysis of the characteristics of the marine environment, which affect the transfer of sound energy in it. It is shown that the temperature, salinity and pressure used in the calculation of the speed of sound in water by known formulas affect not directly but indirectly, through the formation of certain structures in the aquatic environment (mono-, nano- and supramolecular), which define those " abnormal "features of sound that recorded experimentally. Negative anomaly absorption of sound energy at low frequencies can be created on condition synchronization in space and time effects of changes in the structure of water while passing acoustic wave with the properties of the phenomenon itself (sound). The theory of Very long sound distribution should also take into account the effect of resonance, as a mechanism to reinforce a sound signal by coherent vibration process in the marine environment. At first sight, this may be due to coincidence acoustic wave periods and the period of natural oscillations compressibility of sea water.
Anomalous properties of water and their influence on hydroacoustic technologies
Keywords: структура води; аномальні властивості води; гідроакустика; підводний звуковий канал; позитивний зворотний зв'язок; anomalous properties of water; water structure; hydroacoustic; underwater sound channel positive feedback